A Novel Repair Idea on Nasal Sidewall Defect in Asians: Local Tissue Regeneration. Issue 5 (July 2021) - Zhang, Minchen; Gao, Weicheng; Hu, Yuting; Zhang, Jie; Liu, Songjian; Zhuo, Ran
Abstract : Background: The traditional ways indicate using different types of flap to repair the nasal sidewall defect, but the scar in the donor area or bloated flap is a problem that cannot be ignored. This study propose the clinical application of the principle of tissue regeneration priority in small defects (defect diameter <1.0 cm) of nasal sidewall. Methods: A retrospective study of 3 patients experienced the tumor excision and tissue regeneration healing in situ from January 2019 to January 2020. In this group, the nasal sidewall defect was treated with wound moist theory, preventing infection, to promote the wound regeneration and repair. Result: The longest follow-up time was 8 month, all patient undergone half a year follow-up at least. One of them were left small sunken scars but all of them healed up well and satisfied with the results. Conclusion: When dealing with the small defect of the skin and soft tissue on the nasal sidewall (defect diameter <1.0 cm), this article provided a new idea that is application of the priority principle for tissue regeneration repair rather than traditional flap used for 1-stage repair. For the small defects of the skin and soft tissue on the nasal sidewall, the tissue regeneration and natural repair in situ can achieve satisfactory effects. More importantly, it has the advantages of simplicity, ease of operation, and fewer complications.